Do Export Promotion Agencies Promote New Exporters? - Cruz, Marcio (World Bank Group, Washington, DC, 2014)
Do export promotion agencies impact the probability of non-exporting firms to export? In the last decade many countries have introduced export promotion agencies to support their firms to deal with asymmetric information problems and make feasible additional gains from trade. Some recent studies have found that the support of these agencies has been effective with respect to the intensive and extensive margins of trade. Nevertheless, because of the lack of information on non-exporting firms, few of them analyze their impact on the probability of promoting new exporters. This paper evaluates the impact of the Brazilian Trade and Investment Promotion Agency (Apex-Brasil) on firms' export status using a unique firm-level dataset that covers the full manufacturing sector in Brazil. To identify the impact of Apex's assistance on firms' export propensity, the paper relies on a procedure of matching difference-in-difference estimators. The empirical results show evidence of the program's positive impact on the probability of promoting new exporters. The effect is heterogeneous according to firms' size categories and sectors. Furthermore, the findings suggest that the program has spillover effects. Although the evidence of positive effect is robust, the low propensity to export for both the treated and the control groups reinforces the importance of other firms' determinants (for example, productivity), which is widely emphasized by the trade literature.